Polisi dan Sumber Daya Manusia: Studi Assessment Center Berbasis Merit System di Polda Lampung - Tanicha Aprilia; Intan Fitri Meutia (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2019)
The police is a goverment organization whose function is to protect and serve the people of Indonesia. To carry out these duties and functions properly, the Police seeks to create police personnel who have considered capable enough in carrying out tasks with high responsibility. In that way, it is expected that positions filled by these personnel can bring profits to the Lampung Regional Police agency to construct the image and excellent service for the community. This research is a qualitative research, using a descriptive approach through interviews and observation. The conclusion of this research are 5 principles reflected in the Police's efforts to create competitive human resources through assessment center based on merit system, and that are (1) objective principle, Assessment Centerhave consideration material in determining assessment results, (2) accountable principle, namely the implementation and results of the assessment center can be accounted for, (3) nesesitas principle, that is the implementation of the assessment center itself is carried out according to the needs of the National Police organization both in the headquarters and in the regional police, (4) transparency principle, the result of assessmentmonitored by the Career Advisory Board (DPK) in order to the assessment center process always runs well and according to procedures, and the last (5) independent principle, where the process and results of the assessment center are not affected by other parties.